Impact of Covid pandemic on the natural population increase in North Macedonia - Janeska, Verica; Lozanoska, Aleksandra (Institute of Social Sciences-Belgrade, 2021)
Objectives - The Covid-19 pandemic has brought significant consequences and implications, changing many social, economic, healthcare and environmental determinants, as well as demographic processes. Particularly emphasized is its impact on the changes in the total population increase. It is mainly determined by the natural population increase, and relatively less by migratory movements, due to limited international migrations in the new conditions worldwide. The aim of the research is to provide knowledge on the implications that the Covid-19 pandemic has had to date on the natural population increase in North Macedonia, by analyzing the relevant data and indicators published thus far. It offers knowledge about the essential features of the manifested changes, their key determinants and long-term impact in terms of intensified demographic ageing. Methodology - The methodological approach of the study involves application of desk research and analysis of the State Statistical Office data related to natural population increase, as well as marriages and divorces. Data and indicators for the natural increase and its components (live births and deaths) for the last 15 years are presented. A more detailed, per-month analysis of the changes in the natural increase, marriages and divorces is conducted for 2019 and 2020, using the available statistical data, which for 2020 implies using preliminary data. Implications – The analysis of the preliminary data on the natural population increase, as well as of marriages and divorces, indicates the significant changes in 2020, which were mostly caused by the Covid-19 pandemic. Having in mind their long-term implications, further decrease in the natural population increase and total population growth can be expected, as well as acceleration of the process of demographic ageing. Once the pandemic is over, North Macedonia should focus on the revision of the current population policy and create comprehensive measures to mitigate the consequences of these unfavorable changes.
Extended Abstract published in a Book of Abstracts
Keywords: Natural population increase; Life-births; Deaths; Marriages; Divorces; North Macedonia